Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

Pedagogic change by Zambian primary school teachers participating in the OER4Schools professional development programme for one year - Hennessy, Sara; Haßler, Björn; Hofmann, R. (Research Papers in Education, 2016)
Supporting and upskilling teachers are essential to enhancing the quality of learning in developing contexts – the focus of Education For All – yet little evidence exists concerning what kinds of teacher education are actually most effective and what changes in ‘quality’ are desired and feasible. This paper illustrates how a concrete, research-informed school-based, model of professional development in sub-Saharan Africa can address the quality agenda. It reports on a trial of a pioneering, multimedia programme supporting interactive mathematics and science teaching using open educational resources and classroom digital technology, where available. The programme was carefully adapted to the Zambian context and ran weekly for one school year with 12 teachers in a low-resourced primary school. The study examined the impact on teachers' thinking and classroom practices. Data were derived from observations, lesson and workshop recordings, teacher interviews, portfolios and audio diaries. Through a teacher-led workshop approach and trialling new pedagogical strategies, teachers raised their expectations of pupils, adapted to learners’ knowledge levels, used more practical and group work, and integrated technology use. Pupils built deeper understanding of subject matter, were actively engaged, worked collaboratively and used digital technologies for problem-solving.
Keywords: C:sub-Saharan Africa; CAREER development; EDUCATION -- Study & teaching; GRADUATE education; PROFESSIONAL education; TEACHER training; ZAMBIA; Zambia; __:import:01; __:match:final; __:matched; __:study_id:2099887; ___working_potential_duplicate; __finaldtb; digital technology; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development